2015
DOI: 10.1109/tlt.2014.2363663
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Interpretative Views of Learners’ Interaction Behavior in an Open Learner Model

Abstract: In this paper, we discuss how externalizing learners' interaction behavior may support learners' explorations in an adaptive educational hypermedia environment that provides activity-oriented content. In particular, we propose a model for producing interpretative views of learners' interaction behavior and we further apply this model to INSPIREus for visualizing specific indicators. In the proposed approach, we collect raw data from learners' interaction at various grains, model the state of interaction using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…However, no feedback which includes individualized recommendations and guidance based on the LA results has been provided in the past research. The study of Papanikolaou (2015) tells us that the participants benefit from the data about their own learning processes in terms of getting effective feedback. Similarly, another study by Arnold and Pistilli (2012) concur well with this article and argue that most of the students find getting LA results as feedback useful in terms and more than half of them asked for to use this approach in other courses, as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, no feedback which includes individualized recommendations and guidance based on the LA results has been provided in the past research. The study of Papanikolaou (2015) tells us that the participants benefit from the data about their own learning processes in terms of getting effective feedback. Similarly, another study by Arnold and Pistilli (2012) concur well with this article and argue that most of the students find getting LA results as feedback useful in terms and more than half of them asked for to use this approach in other courses, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-studies and usability studies of prototypes could be especially useful to determine the right balance for a given context. More specifically in terms of design features, our work points to the value of providing "expressiveness" to the learner model visualization with summary features (such as the learning gauge) that could facilitate the interpretation of the information presented (Papanikolaou, 2015) and can assist the learners in various tasks supported by the OLM (such as finding the right content). This line of research bridges OLM and an emerging area of learning analytics shown to learners (Bodily & Verbert, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has taken the issue of complexity and interpretability further by extending the OLM with more elaborate features such as indicators of e↵ort, progress, or working style (Papanikolaou, 2015). This type of work bridges the gap between OLM and Learning Analytics dashboards (Verbert et al, 2013), in which the data shown to learners include not only estimations of knowledge-related attributes, but also broader learning traces and other information provided by teachers.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to the examples above that can permit other users to view and interact about an individual’s learner model, several OLMs have allowed learners to view each other’s learner models (e.g. Bull and Britland 2007; Bull et al 2007; Hsiao et al 2013; Shi and Cristea 2014; Papanikolaou 2015). Such approaches are relevant as a starting point to considering negotiated learner modelling, since they have already examined the issue of visualising the learner model not only to the user the model represents but also to other parties.…”
Section: Negotiated and Other Types Of Interactive Learner Modellingmentioning
confidence: 99%